Adaptation Of Arabic Script Into Pegon Sunda In A Kitab Of Tijan Al-Dharari - Ramdani, Vierry Firdaus; Syafi'i, Muhammad Zarkasyi; Tatang, Tatang (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2025)
The Sundanese Pegon script is a modified Arabic script used in writing Sundanese texts, especially in pesantren. It plays an important role in Islamic learning, allowing santri to understand religious texts in their own language. Over time, the Sundanese Pegon script underwent phonological and structural adaptations to suit the Sundanese language. This research examines the adaptation of Arabic script into Sundanese Pegon script in the book of Tijan al-Darari as part of cultural preservation and transmission of Islamic values. Qualitative research method with descriptive-analytical approach is used to analyze the phonological and morphological characteristics of Sundanese Pegon script in the manuscript. The results show that the Sundanese Pegon script underwent vowel and consonant adjustments to match Sundanese phonology. In addition, its visual and structural modifications reflect the combination of Islamic values and local culture. Thus, the Sundanese Pegon script not only functions as a means of communication, but also as a means of religious education and preservation of Sundanese cultural identity in the pesantren environment.